Analysis of Superior Potential and Competitiveness of the Agricultural Sector in Tabanan Regency - Ni Komang Ayu Fitri Adi Cahyani; Dwi Putra Darmawan; Gede Mekse Korri Arisena (Universitas Udayana, 2021)
The agricultural sector in Tabanan Regency not only plays a role in food security, but also contributes significantly to sources of income. During the last five years the agricultural sector in Tabanan Regency has also contributed significantly to the GRDP of Tabanan Regency. The purpose of this study is to identify the superior potential of the agricultural sector in Tabanan Regency and to identify the competitiveness of the agricultural sector in Tabanan Regency. This study uses secondary data sourced from the Central Statistics Agency (BPS) of Tabanan Regency and Bali Province. There are two analyzes used in this study, namely Location Quotient (LQ) analysis and Shift Share analysis. The results of research using Location Quotient (LQ) analysis show that the agricultural sector is included in the category of leading sectors in Tabanan Regency. This is indicated by the Location Quotient (LQ) value that is greater than one. While the results of the study using Shift Share analysis show that the agricultural sector in Tabanan Regency is included in the category of sectors that have fast competitiveness compared to reference areas, this is because the value of Differential Shift shows a positive value.